Henry James and Neuroscience: Cognitive Universals and Cultural Differences - Armstrong, Paul B. (The Henry James review, 2018)
Henry James's dramatizations of consciousness provide a kind of knowledge about the life of our embodied minds that escapes the techniques of science, but neuroscience can assist literary analysis by elucidating the cognitive processes underlying various narrative techniques. James's characteristic representational strategies are aesthetic instruments for exploring different aspects of perceptual experience. James was fascinated by our biocultural hybridity-the paradox that everyone in our species has the same cognitive equipment with which we construct disparate, even sometimes incommensurate worlds. His techniques are grounded on universal, neurobiologically based processes of cognition that can give rise to different cultural and epistemological practices.